Pemetaan Daerah Rawan Erosi Di DAS Wae Batu Merah Kota Ambon - Intopiana, Lidia V.; Putuhena, Jusmy D.; Boreel, Aryanto (Universitas Pattimura, 2020)
This study aimed to identify the factors that cause erosion, map erosion-prone areas, and determine conservation directions that can be carried out on regions indicated by erosion in the Wae Batu Merah watershed. In this study, erosion forming parameters will be overlapped. The USLE (Universal Soil Loss Equation) method was used as a parameter to create erosion. The results showed that erosion factors that greatly affected the erosion incidence in the Wae Batu Merah watershed, namely, slope factors and crop management factors and conservation measures, and as much as erosion were dominated by very large classes with an area of ​​558.21 ha or 52.67% alone. The smallest is the medium class, with an area of ​​54.57 ha or 5.15%. Conservation directives carried out on regions indicated by erosion in the Wae Batu Merah watershed were the direction of the vegetative method, which is reforestation, planting trees in the form of durian trees, and GMO sengon trees, making parks in residential areas, and building mechanical terraces.